Direct hydroxylation of benzene to phenol in a microstructured Pd-based membrane reactor - Bortolotto, Laurent (KIT Scientific Publishing, 2011)
The gas phase direct hydroxylation of benzene into phenol with hydrogen and oxygen, as initially described by Niwa in 2002, was realized in a newly developed double-membrane reactor. In the concept described by Niwa, a dense Pd membrane is used for the (safe) dosage of dissociated hydrogen species into the tubular reaction zone, where it reacts with gas phase oxygen to form surface species capable of directly converting benzene into phenol in a single-step process.